Clinical and genetic data of 22 new patients with SMAD3 pathogenic variants and review of the literature. Issue 5 (10th March 2020) - Chesneau, Bertrand; Edouard, Thomas; Dulac, Yves; Colineaux, Hélène; Langeois, Maud; Hanna, Nadine; Boileau, Catherine; Arnaud, Pauline; Chassaing, Nicolas; Julia, Sophie; Jondeau, Guillaume; Plancke, Aurélie; et al.
Abstract: Background: Pathogenic SMAD3 variants are responsible for a cardiovascular phenotype, mainly thoracic aortic aneurysms and dissections. Precocious identification of the vascular risk such as aortic dilatation in mutated patients has a major impact in terms of management, particularly to avoid dissection and sudden death. These vascular damages are classically associated with premature osteoarthritis and skeletal abnormalities. However, variable expressivity and incomplete penetrance are common with SMAD3 variants. Methods: To investigate the clinical variability observed within SMAD3 patients, we reviewed the phenotypic and genetic data of 22 new patients from our Centre and of 133 patients reported in the literature. From this cohort of 155 mutated individuals, we first aimed to delineate an estimated frequency of the main clinical signs associated with SMAD3 pathogenic variants and, then, to look for genotype‐phenotype correlations, mainly to see if the aortic phenotype (AP) could be predicted by the SMAD3 variant type. Results: We showed, herein, the absence of correlation between the SMAD3 variant type and the occurrence of an AP in patients. Conclusion: Therefore, this report brings additional data for the genotype‐phenotype correlations of SMAD3 variants and the need to explore in more detail the effects of genetic modifiers that could influence the phenotype. Abstract : Pathogenic SMAD3 variants are responsible for a cardiovascular phenotype, mainly thoracic aortic aneurysms and dissections, with variable expressivity and incomplete penetrance. To investigate the clinical variability observed within SMAD3 patients, we reviewed the data of 22 new patients from our Centre and of 133 patients reported in the literature. We first aimed to delineate an estimated frequency of the main clinical signs associated with SMAD3 pathogenic variants and, then, to look for genotype‐phenotype correlations. We showed herein the absence of correlation between the SMAD3 variant type and the occurrence of an aortic phenotype in patients. This report brings additional data for the genotype‐phenotype correlations of SMAD3 variants and the need to explore in more detail the effects of genetic modifiers that could influence the phenotype.